Proyecto Integral De Renovación Urbana Malecón Río Guatiquía en la ciudad de Villavicencio (2021)
This paper addresses the issue of unplanned land occupation on city edge land, through the case of settlements and neighborhoods located on the banks of the Guatiquia River in the city of Villavicencio, which leads to environmental problems, social, cultural and urban. In this way, from the academic field, this research collects and analyzes information on the sector, elaborates a diagnosis of it, and through the analysis of theoretical concepts and reference projects, an urban proposal is generated in which it is intended to solve the problems. problems previously described, in order to improve the relationship between the city and the river, and seeing the edge of the city as a space of urban opportunity.